Isolation and Characterization of Bergapten from the Root Bark of Ficus exasperata (Vahl) with Hypoglycemic Activity - Famobuwa, O. E.; Agbowuro, A. A.; Adekunbi, E. A.; Akinwale, M. A. (Recent Developments in Chemistry and Biochemistry Research Vol. 5, 2024)
The present study reports the isolation and characterization of bergapten, a furocoumarin, as a major constituent in the root bark of Ficus exasperata, as well as its hypoglycemic activity. Despite the wide ethnomedicinal applications of Ficus exasperata, little is known about the active principles responsible for the observed biological effects, thus limiting opportunities for further therapeutic applications. Phytochemical investigation of extracts from the genus Ficus revealed the presence of several bioactive secondary metabolites, including flavonoids, alkaloids, phenolic acids, steroids, saponins, tannins, terpenoids, and coumarins. The bioassay-guided chemical investigation of F. exasperata root bark resulted in the isolation of a furocoumarin (D-1), which was shown to be partly responsible for the acclaimed anti-diabetic effect of the plant. It is thus research-worthy to unravel the precise mechanism of action of the molecule as a hypoglycemic agent, followed by rational structural modification to optimize it for potency and safety.